A series active power filter controlled by personal computer - Sepúlveda, João (2003)
This paper describes work that is being done in the design and implementation of a series active power filter for electrical power quality purposes. This type of filter is able to compensate for the following voltage related problems in the power grid: short blackouts for a few cycles, voltage distortion due to harmonics on a repetitive basis, voltage unbalance in three-phase systems, voltage flicker (subharmonics) and momentary over or under voltages. The main objective of the work described in the paper is to build a series active filter controlled by a personal computer with a standard multifunction data acquisition PCI bus card, because of its relative low cost and versatility. This PC based solution presents some difficulties since the control of a series active filter is a kind of application which requires a fast controller which that does not miss samples and where all real-time deadlines must be met each and every time, or the system will not operate properly. These characteristics imply that this application falls in the “hard real-time” control category. In the paper, some results are presented and some conclusions are taken using two different operating systems. Furthermore, a comparison with a microcontroller based implementation will be made.